2013
DOI: 10.5812/hepatmon.13136
|View full text |Cite
|
Sign up to set email alerts
|

Serum Iron Markers in Patients WithChronic Hepatitis C Infection

Abstract: BackgroundPatients with chronic hepatitis C (CHC) often have elevated serum iron markers, which may worsen liver injury.ObjectivesThe aim of this study was to investigate the possible correlations between iron metabolism serum markers, HCV viral load, and liver disease severity in treatment-naive patients with chronic hepatitis C infection.Patients and MethodsEighty five patients with untreated hepatitis C chronic infection were investigated.ResultsTwenty one patients (24.7%) had elevated serum iron levels, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 20 publications
4
13
0
Order By: Relevance
“…Furthermore, iron accumulation in HBV and HCV infections [33] causes liver damage due to oxidative stress, which increases hepatocyte necrosis/apoptosis, hepatic stellate cell activation and fibrogenesis through the proliferation of actin and collagen [34] , [35] . However, iron markers do not differ significantly in patients with low or high HCV viremia [36] . Serum ferritin and transferrin levels appear to play an important role in determining the severity of liver disease related both to liver fibrosis and necroinflammatory activity but not the presence of infection.…”
Section: Resultsmentioning
confidence: 84%
“…Furthermore, iron accumulation in HBV and HCV infections [33] causes liver damage due to oxidative stress, which increases hepatocyte necrosis/apoptosis, hepatic stellate cell activation and fibrogenesis through the proliferation of actin and collagen [34] , [35] . However, iron markers do not differ significantly in patients with low or high HCV viremia [36] . Serum ferritin and transferrin levels appear to play an important role in determining the severity of liver disease related both to liver fibrosis and necroinflammatory activity but not the presence of infection.…”
Section: Resultsmentioning
confidence: 84%
“…Many previous studies suggested excessive iron accumulation in the hepatocyte accelerate hepatocellular damage, liver fibrosis, and eventually increase risk of hepatocellular carcinoma. 18 , 19 There were several studies to determine regulatory system of iron metabolism to maintain homeostasis and some studies proposed transferrin and hepcidin, which play a crucial role in iron metabolism, as surrogate markers for predicting severity of liver disease in the patients with chronic hepatitis C. 20 , 21 Recently, Xu et al performed proteomic study to identify reliable non-invasive serum biomarkers of liver fibrosis in patients with CHB, and they reported decreased level of serum transferrin in cirrhotic patients compared with non-cirrhotic patients. 22 But there was no other study which validated serum transferrin as liver fibrosis marker in patients with CHB.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of HCV is estimated to be 3% worldwide; out of which, approximately 170 billion people are affected with the hepatitis C antibody. 1,2 Around 20% of chronic hepatitis C (CHC) cases progressed to cirrhosis that is a life-threatening hepatic condition. 2 Other risk factors associated with CHC are decompensated liver disease and hepato-cellular carcinoma, which ultimately requires liver transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Around 20% of chronic hepatitis C (CHC) cases progressed to cirrhosis that is a life-threatening hepatic condition. 2 Other risk factors associated with CHC are decompensated liver disease and hepato-cellular carcinoma, which ultimately requires liver transplantation. Different viral factors (such as genotype and baseline viral load), comorbidities, and genetic background of the host characterize the outcomes of HCV infection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation